A soybean 101-kD heat shock protein complements a yeast HSP104 deletion mutant in acquiring thermotolerance. - Lee, Y R (1994)
A cDNA clone encoding a 101-kD heat shock protein (HSP101) of soybean was isolated and sequenced. Genomic DNA gel blot analysis indicated that the corresponding gene is a member of a multigene family. The mRNA for HSP101 was not detected in 2-day-old etiolated soybean seedlings grown at 28 degrees C but was induced by elevated temperatures. DNA sequence comparison has shown that the corresponding gene belongs to the Clp (caseinolytic protease) (or Hsp100) gene family, which is evolutionarily conserved and found in both prokaryotes and eukaryotes. On the basis of the spacer length between the two conserved ATP binding regions, this gene has been identified as a member of the ClpB subfamily. Unlike other Clp genes previously isolated from higher plants, the expression of this soybean Hsp101 gene is heat inducible, and it does not have an N-terminal signal peptide for targeting to chloroplasts. Transformation of the soybean Hsp101 gene into a yeast HSP104 deletion mutant complemented restoration of acquired thermotolerance, a process in which cells survive an otherwise lethal heat stress after they are given a permissive heat treatment.